Bahasa Indonesia: Three Cases of the 2020 Regional-Head Election in Jambi - Arfan; Sinta Rahmatil Fadhilah; Siti Aminah (Bestuurskunde: Journal of Governmental Studies, 2021)
The 2020 Regional Head Election continued to show the presence of Kinship Politics at the regional level, including in Jambi. The incumbents encouraged their family members to run as candidates in the election for Governor and Deputy Governor of Jambi, Regent of Batang Hari, and Mayor of Sungai Penuh. Surprisingly, Kinship politics failed to win in all three locations. This study aimed to analyze the failure of Kinship politics in the 2020 Regional Head Election in Jambi (namely Yuninta Asmara-Muhammad Mahdan in Batang Hari Regency, Cek Endra-Ratu Munawaroh in the election for the Governor of Jambi, and Fikar Azami-Yos Andrino in the election for Mayor of Sungai Penuh) through an independent observation from November 2020 to January 2021, as well as documentation of data and news related to the 2020 Regional Head Election in Jambi. The failure of the three candidate pairs was due to: first, the lack of public trust in the incumbent's family; second, the lack of campaign fund contributions; third, lack of promotions for the candidate pairs on social media; fourth, the lack of political communication between candidates, political parties, and constituents, while the alternative candidates optimally, effectively and efficiently managed the campaign team, campaign logistics, and their constituents; five, the alternative candidates' track records showed better credibility and capability; and six, better electability and acceptability of the alternative candidates. This study concluded that Jambi could be an example of minimizing the dominance of Kinship politics by using an alternative candidate who has a solid team, good online campaign management, and effective logistics management. Jambi can be a barometer of the rise of real democracy.